Steroid cell tumour of the ovary: a case report with review of literature - M., Fathima Seles; Revathy, M.; Kanchana, Madurai Padmanabhan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Virilising ovarian tumours account for less than 5% of all ovarian tumours. A steroid cell tumour (SCTs) of the ovary comes under the sex cord stromal tumours and accounts for only 0.1% of all ovarian tumours. Almost 75% are functioning tumors with production of androgenic hormones causing virilisation and cushingoid features. They are usually unilateral, benign with only 25-45% malignant cases. Here authors report the incidence of steroid cell tumour in our institution and discuss about a 37-year-old woman with steroid cell tumour, not otherwise specified who presented with oligomenorrhea followed by amenorrhea, secondary infertility and signs of virilisation.